PEO-based polymer blend electrolyte for composite structural battery - Gucci, Francesco; Grasso, Marzio; Shaw, Christopher; Leighton, Glenn J. T.; Marchante Rodriguez, Veronica (Taylor & Francis, 2023)
High mechanical strength and ionic conductivity of solid-state electrolyte (SSE) are currently conflicting targets that are very difficult to achieve. Polyethylene oxide (PEO) is one of the most common polymers adopted for SSE because of its very high ionic conductivity, but its mechanical strength is very low. This work discusses the manufacturing and testing of PEO blends using polysulfone (PSf) and Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to assess the mechanical response under microtensile testing and the ionic conductivity with electrochemical impedance spectroscopy (EIS). Mechanical tests demonstrated a beneficial effect of LiTFSI with significant increase in maximum stress and ductility measured as strain at failure. The blending of PEO and PSf showed promising conductivity values at room temperature with the 90–10 PEO-PSf composition achieving the highest value (1.06 × 10−6 S/cm) and for the 70–30 composition achieving the highest maximum stress (3.5 MPa) with a conductivity of 3.12 × 10−7 S/cm.
Keywords: Solid state electrolyte; lithium; electrochemical impedance spectroscopy; polymer blend